Title IX Then and Now at Old Dominion University - Brendan O'Hallarn; Angela Eckhoff; D'Andra Seymore (University of Kansas Libraries, 2016)
Old Dominion University celebrates its pioneering role in addressing the landmark federal gender equity legislation known as Title IX, noting with pride that it was among the first universities in the country to offer scholarships for female studentathletes. What the popular portrayal of Old Dominion as a trailblazer misses is the internal struggle over gender-equity issues within the University at the time Title IX was being implemented. A 1975 letter discovered in the Old Dominion University Archives and Special Collections provides unique insight into that conflict, and offers an opportunity to analyze the University's commitment to gender equity through both a historical and modern lens. A hermeneutical analysis of the 40-year-old letter was used to inform a question line for six modern-day female administrators at the University. Echoes of 1975 are plentiful in their words, and offer new insight into how gender-equity struggles have changed through the decades in higher education.